A Naive approach: Translation of Natural Language to Structured Query Language - Rautaray, Jyotirmayee; Mishra, Pranati (EAI Endorsed Transactions on Scalable Information Systems, 2023)
A database is a major source of information which plays an important role in our life. Information retrieval from the database requires formulating a querythatisunderstandablebythecomputerinordertoproducedesiredoutput. Generally, databases work with structured query language (SQL). But a naive user usually unfamiliar with the structured query language as well as structure of the table in the database. Hence, it becomes very difficult for the naïve-user to collect the desired information. This paper provides a solution to this problem and it enables users to retrieve information through natural language, such as English language. Being able to access information from the database by using natural language bridges the man-machine gap. Tokenization, lexical analysis, syntactic analysis, semantic analysis, and other complex stages are all involved in converting a natural language query into a SQL query. The purpose of this paper is to translate natural language queries into Structure Query Language queries, allowing non-technical people to get connected to databases and to gather the required information.